(1032) Planning and Necessary Changes التخطيط والتغييرات الضرورية - El-Sayed Abdel-Mawla (INP., 2020)
The primary driver behind the adoption of national planning is the state's recognition of its crucial role in initiating and managing economic development. Given the structural rigidities and limitations of existing socio-economic systems, state intervention is deemed necessary to drive change. National plans, formulated as sets of quantitative goals and clearly defined tasks, serve as essential instruments for policy coordination and rational decision-making.